2013
DOI: 10.1136/jclinpath-2012-201278
|View full text |Cite
|
Sign up to set email alerts
|

IGFBP-5 overexpression as a poor prognostic factor in patients with urothelial carcinomas of upper urinary tracts and urinary bladder

Abstract: IGFBP-5 plays an important role in tumour progression in UC. Its overexpression is associated with advanced tumour stage and conferred poorer clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 29 publications
1
36
0
Order By: Relevance
“…Circulating concentrations of insulin-like growth factor (IGF) and certain insulin-like growth factor binding proteins (IGFBP) are associated with higher risk and worse outcome among patients with bladder, as well as colorectal, prostate and breast cancers (41). Thus, it is possible that patients with worse glycemic control had lower levels of insulin in the serum and thus improved prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating concentrations of insulin-like growth factor (IGF) and certain insulin-like growth factor binding proteins (IGFBP) are associated with higher risk and worse outcome among patients with bladder, as well as colorectal, prostate and breast cancers (41). Thus, it is possible that patients with worse glycemic control had lower levels of insulin in the serum and thus improved prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, only 29 of the 106 UTUC patients with pT3 or pT4 stage and/or nodal involvement received adjuvant chemotherapy. The criteria for the clinicopathological evaluation were essentially identical to our previous studies 23-28.…”
Section: Methodsmentioning
confidence: 99%
“…In this formula, i represents the intensity of the stained tumor cells (0-3+), and Pi is the percentage of stained tumor cells for each intensity varying from 0% to 100%, with an obtained score ranging from 100-400. The score 100 indicated that 100% of tumor cells were negative, and 400 indicated that 100% of tumor cells showed an intense, strong staining (3+) 23-28. Concordance for interpretation of RNF128 between the two pathologists was above 90%.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies investigated the prognostic impact of various tissue-based molecular markers that are related to cellular processes such as cell adhesion (Metalloproteinase-9, E-cadherin [33], ParvB [34], snail [35], b-catenin[36]), cell signaling (EGFR[37], EMP3 [38], HER2 [4], PI3K/AKT [39, 40], IGFBP-5 [41], mTOR [42]), angiogenesis (Hypoxia-inducible factor-1[43]), cell proliferation (Ki67[44], p27 [45],cyclin D[46], NF- κ B [47], Aurora-A[48]), cell transport (GRP78 [49]) and apoptosis (bcl-2, survivin [50]). Recently, Wu et al compared the genome-wide mRNA expression profile using digital gene expression sequencing of tumors and matched normal tissues in 10 UTUC patients.…”
Section: Potential Biomarkers From Gene Expression Profilingmentioning
confidence: 99%